2016
DOI: 10.1007/s00125-016-4169-z
|View full text |Cite
|
Sign up to set email alerts
|

Interrupting prolonged sitting in type 2 diabetes: nocturnal persistence of improved glycaemic control

Abstract: anzctr.org.au ACTRN12613000576729 FUNDING: : This research was supported by a National Health and Medical Research Council (NHMRC) project grant (no. 1081734) and the Victorian Government Operational Infrastructure Support scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
138
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(151 citation statements)
references
References 36 publications
7
138
2
Order By: Relevance
“…When considering T2D patients, introducing light walking breaks reduced 7 h glucose, insulin, and C-peptide, compared with prolonged sitting (Dempsey et al, 2016b). The same authors verified that the glycemic improvements that arise from breaking up sedentary time persist until the next morning, indicating that there may be medium to long term benefits in T2D patients (Dempsey et al, 2016a). Even though these experimental findings are of great importance (because they allow establishing causal relationships between BST and metabolic outcomes) the laboratorial settings and protocols in which they are performed, do not mimic real-life conditions and limit their ecological transfer.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…When considering T2D patients, introducing light walking breaks reduced 7 h glucose, insulin, and C-peptide, compared with prolonged sitting (Dempsey et al, 2016b). The same authors verified that the glycemic improvements that arise from breaking up sedentary time persist until the next morning, indicating that there may be medium to long term benefits in T2D patients (Dempsey et al, 2016a). Even though these experimental findings are of great importance (because they allow establishing causal relationships between BST and metabolic outcomes) the laboratorial settings and protocols in which they are performed, do not mimic real-life conditions and limit their ecological transfer.…”
Section: Discussionmentioning
confidence: 89%
“…When considering experimental evidence (Dunstan et al, 2012; Howard et al, 2013; Latouche et al, 2013; Larsen et al, 2014; Bailey and Locke, 2015; Dempsey et al, 2016a,b), breaking up prolonged sedentary time with light ambulation is still an effective strategy for improving glucose regulation, which further clarifies the need to expand current diabetes-related PA guidelines, by introducing regular breaks in prolonged sedentary time (Dempsey et al, 2016c). Dunstan et al (2012) found that breaking up sedentary time with LIPA bouts reduced 5 h glucose iAUC by 24% and 5 h insulin iAUC by 23%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Healy et al (11) reported that increased breaks in SED-time were beneficially associated with metabolic profile, independent of MVPA and also total SED-time. More recent studies confirmed the benefits from interrupting prolonged sitting with brief bouts of light-intensity PA (LPA) in patients with type 2 diabetes (12)(13)(14).…”
mentioning
confidence: 93%